Geographic Inequities in Liver Allograft Supply and Demand: Does it Affect Patient Outcomes?. Issue 3 (March 2015) - Rana, Abbas; Kaplan, Bruce; Riaz, Irbaz B.; Porubsky, Marian; Habib, Shahid; Rilo, Horacio; Gruessner, Angelika C.; Gruessner, Rainer W.G.
Abstract : Background: Significant geographic inequities mar the distribution of liver allografts for transplantation. Methods: We analyzed the effect of geographic inequities on patient outcomes. During our study period (January 1 through December 31, 2010), 11, 244 adult candidates were listed for liver transplantation: 5, 285 adult liver allografts became available, and 5, 471 adult recipients underwent transplantation. We obtained population data from the 2010 United States Census. To determine the effect of regional supply and demand disparities on patient outcomes, we performed linear regression and multivariate Cox regression analyses. Results: Our proposed disparity metric, the ratio of listed candidates to liver allografts available varied from 1.3 (region 11) to 3.4 (region 1). When that ratio was used as the explanatory variable, the R 2 values for outcome measures were as follows: 1-year waitlist mortality, 0.23 and 1-year posttransplant survival, 0.27. According to our multivariate analysis, the ratio of listed candidates to liver allografts available had a significant effect on waitlist survival (hazards ratio, 1.21; 95% confidence interval, 1.04–1.40) but was not a significant risk factor for posttransplant survival. Conclusion: We found significant differences in liver allograft supply and demand—but these differences had only a modest effect on patient outcomes. Redistricting and allocation-sharing schemes should seek to equalize regional supply and demand rather than attempting to equalize patient outcomes. Abstract : This analysis of the UNOS database for listings and outcomes in liver transplantation showsthat differences among regions in donor organs available to listed recipient ratios adversely affect waitlist survival but not posttransplant outcomes. Supplemental digital content is available in the text.